Teaching Anxiety Among EFL Student Teachers During the Teaching Practicum - Wulandari Pasaribu; Sri Lestari (EduLine: Journal of Education and Learning Innovation, 2023)
This study investigated the sources of teaching anxiety experienced by EFL student teachers and their strategies to overcome their teaching anxiety. The study used a qualitative research design with close-ended questionnaires and semi-structured interviews to collect the data. The obtained data were categorized and transcribed to be analyzed qualitatively. The findings revealed seven main factors that caused teaching anxiety including; evaluation, students’ behaviors, self-confidence, fear of making mistakes, time management, lesson delivery, and teaching preparation. Student teachers implemented several strategies to overcome EFL student teachers’ anxiety including; humor and positive thinking, good planning and preparation, building a good relationship, practicing mindfulness, creating fun English learning activities, and giving a reward. The results provide important implications for further research development in educational practices, specifically in managing teaching anxiety among prospective teachers.